2018
DOI: 10.1007/s11095-018-2345-1
|View full text |Cite
|
Sign up to set email alerts
|

Surface Enrichment and Depletion of the Active Ingredient in Spray Dried Amorphous Solid Dispersions

Abstract: The surface concentration of a SDD can be significantly different from the bulk concentration. The main results of this work are consistent with the notion that the relative surface tensions control surface enrichment or depletion. Besides, the relative diffusion rates of the components and the strength of their interactions may also affect the surface composition of the SDDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“… 25 , 29 , 30 X-ray photoelectron spectroscopy (XPS) has also been used in the surface characterization of spray-dried ASD particles because of its short penetration depth. 9 , 31 , 32 …”
Section: Introductionmentioning
confidence: 99%
“… 25 , 29 , 30 X-ray photoelectron spectroscopy (XPS) has also been used in the surface characterization of spray-dried ASD particles because of its short penetration depth. 9 , 31 , 32 …”
Section: Introductionmentioning
confidence: 99%
“…Chen et al showed surface tension may also impact surface composition of spray dried ASD particles because solutes with lower surface tension may concentrate on the air–liquid interface when droplets are formed so as to assemble a surface with low free energy. 48 Thus, it is important to note that the process of spray drying is complex with several material properties and processing conditions affecting the particle surface composition. Hence, further systematic studies are warranted to unveil the true mechanisms of such heterogeneity surfaces of spray dried ASD particles.…”
Section: Resultsmentioning
confidence: 99%
“…Through spray drying, aspects of particle morphology, such as shape, size and surface properties, can be highly controlled, which deems the technique appropriate for formulating inhalation powders. Many papers have controlled particle morphology through variations to the inlet temperature, the spray nozzle diameter and properties of the feed solution, such as concentration and viscosity [ 136 ]. The inlet temperature (also known as the drying temperature) and the feed rate are parameters of high importance as they control the rate of evaporation and drying load, which determine particle properties and product yield [ 137 ].…”
Section: The Design Of Carrier Free Formulations Using Coamorphous Solid Dispersions (Cacds)mentioning
confidence: 99%